Benchmarking as a Vocational Quality Improvement Strategy Towards SMK PK (Center of Excellence of Vocational High School) - Aryani, Rita; Fanisyah, Elsah (International Journal of Science and Society, 2024)
Improving the quality of education is an obligation for every educational institution that wants to continue to exist and wants to produce quality graduates to meet the needs and developments of the current times. However, the obstacle is that educational institutions have difficulty determining what strategies must be done to make quality improvement efforts effective. This study aims to know, analyze, and describe benchmarking as a vocational quality improvement strategy towards SMK PK (Center of Excellence of Vocational High School). This study used a qualitative descriptive method with data collection through observation, interview, and observation. Then, the research data is analyzed through data reduction, data display, verification, and conclusions. The results showed that SMK Negeri 44 Jakarta has carried out benchmarking for two years to improve the quality of education and realize it into SMK PK (Center of Excellence of Vocational High School). SMK Negeri 44 Jakarta carries out strategies from the pre-benchmarking period, the benchmarking process, to the plan after the benchmarking is implemented. This research is expected to guide other vocational high schools that want to benchmark to improve quality towards SMK PK (Center of Excellence of Vocational High School).